1971
DOI: 10.1037/h0031080
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and competition of Mexican, Mexican-American, and Anglo-American children of two ages under four instructional sets.

Abstract: A game measuring cooperation and competition was played with pairs of 4-5-year-old Anglo-and Mexican-Americans and with 7-9-year-old Anglo-Americans, Mexican-Americans, and Mexicans. Cooperative play allowed both pair members to receive rewards; competitive play was irrational, allowing no subject to reach his goal. The number of moves pairs took to reach a goal indicated that 4-5-year-olds were more cooperative than the older subjects (p < .001). Among the 7-9-year-old children, Mexicans were most cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
90
1
4

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(109 citation statements)
references
References 6 publications
14
90
1
4
Order By: Relevance
“…Dyads of U.S/ American 8-and 11-year-olds performed dramatically worse than 5-year-olds, the latter of whom spontaneously managed to extract about half of all marbles (see also Kagan & Madsen, 1971). In another recent study 5-year-olds were further found to reciprocally help each other obtain a reward (Melis, Grocke, Kalbitz, & Tomasello, 2016).…”
mentioning
confidence: 91%
“…Dyads of U.S/ American 8-and 11-year-olds performed dramatically worse than 5-year-olds, the latter of whom spontaneously managed to extract about half of all marbles (see also Kagan & Madsen, 1971). In another recent study 5-year-olds were further found to reciprocally help each other obtain a reward (Melis, Grocke, Kalbitz, & Tomasello, 2016).…”
mentioning
confidence: 91%
“…Similar studies have de scribed Mexican-American children as less competitive [Hoppe et al. 1977: Kagan andMadsen, 1971], less rivalrous, less assertive and more submissive [Kagan and Madsen, 1972] than Anglo children. Conversely, other studies have consistently found that Mexican-American children are more co operatively motivated than Anglo children [see Kagan, 1977, for a review].…”
Section: Family As a Unit Of Analysismentioning
confidence: 76%
“…The most common method for studying cooperation and competition in the laboratory is through the use of experimental games. Experimental games have been used in several major studies comparing Mexican-American and Anglo-American children (Avellar & Kagan, 1976;Kagan & Madsen, 1971;Kagan, Zahn, & Gealy, 1977;Knight & Kagan, 1977;Madsen & Shapira, 1970). There were problems in that these studies either confounded ethnicity and socioeconomic status (e.g., Madsen & Shapira, 1970) or did not allow the separation of a desire to win rewards for oneself (individualism or competition) from a desire to win rewards for the group (cooperation or altruism).…”
Section: Cooperation and Competitionmentioning
confidence: 99%
“…Diaz-Guerrero (1979, for example, has reported that Anglos are relatively low in susceptibility to influence and that Mexicans are relatively high in susceptibility to influence. Support for this notion has resulted from phenomenological evaluations (e.g., Heller, 1966;Madsen, 1964), from field observations (e.g., Lewis, 1951;Redfield, 1930), and from laboratory experiments (Avellar & Kagan, 1976;Kagan & Madsen, 1971, 1972a, 1972bKagan, Zahn, & Gealy, 1977;Madsen & Shapira, 1970); but it is difficult to arrive at any firm conclusions based on these studies because they vary widely in their approaches to the study of susceptibility to influence, and because much of the assessment has had serious methodological flaws.…”
mentioning
confidence: 99%